Control synthesis of battery-supercapacitor hybrid power sources system subject to parameter variations and input saturations - Adnan Rafi Al Tahtawi; Arief Syaichu Rohman; Pranoto Hidaya Rusmin; Arwindra Rizqiawan (International Journal of Renewable Energy Development, 2026)
In practical Battery–Supercapacitor Hybrid Power Source (Batt-SC HPS) applications for Electric Vehicles (EVs), parameter variations and actuator input constraints are unavoidable due to changing operating conditions, temperature effects, and physical limitations of power converters and switching devices. These conditions may degrade control performance and potentially lead to closed-loop instability. This paper proposes a control synthesis for a Batt-SC HPS system that guarantees closed-loop stability in the presence of parameter variations and input saturations. A polytopic linear parameter-varying (LPV) model is employed to represent parameter variations in the linearized system around its equilibrium point. Based on this model, a full state-feedback controller is synthesized using simultaneous linear matrix inequalities (LMIs) as sufficient conditions for robust stability across all system vertices. The formulated LMIs incorporate a common quadratic Lyapunov function, L2-gain performance, and sector nonlinearity to explicitly handle control input saturations. Numerical validation is performed under internal resistance variation scenarios using an LMI solver. Closed-loop simulation results show that the proposed controller reduces the battery current RMSE by 70.8% and the DC bus voltage RMSE by 87.4% compared with a conventional PID controller. In comparison with a nominal LTI controller, additional RMSE reductions of 38.31% for battery current and 2.82% for DC bus voltage are achieved. Moreover, the proposed controller maintains comparable energy consumption characteristics, with total energy differences of only 0.22% and 0.11% relative to the PID and LTI controllers. These results demonstrate the potential of the proposed controller for robust stabilization of Batt-SC HPS systems in EV applications.